Legal Protection for Banks in Using Notary Covernotes in Credit Agreements That Cause Bad Loans - Gatot Wahyu Utomo; Amin Purnawan; Soegianto Soegianto (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
The purpose of this study is to analyze: 1) The role of the Notary in making the Covernote in the credit agreement. 2) Legal protection for Banks in the use of Notary Covernotes in credit agreements resulting in bad loans. The approach method used is a sociological juridical approach. The research specifications used are analytical descriptive. This type of data uses primary and secondary data obtained through interviews and literature studies. The data analysis method used is descriptive qualitative. The results of the study concluded: 1) The role of the Notary in making Covernotes on credit agreements in Pangkal Pinang City is not based on statutory regulations. Because neither the UUJN nor the Banking Law regulates the covernote. But here the Notary makes a covernote because he is a partner of the Bank. Because the covernote is not regulated in the Law on Notary Positions (UUJN), then the consequences caused by the covernote apply general legal provisions. Notaries can be sentenced to criminal, if it can be proven in court. 2) Legal protection for banks in the use of notary covernotes in credit agreements is not guaranteed by law. Because the guarantee binding is not perfect. Banks in order to secure and ensure the return of loans given to debtor customers will always ask for guarantees. Guarantee is a means of preventive legal protection. Banks as creditors even use covernotes as the basis for credit disbursement, but still receive repressive protection, based on Articles 1131 and 1132 of the Civil Code.